2021
DOI: 10.3390/biology10040269
|View full text |Cite
|
Sign up to set email alerts
|

Maintaining Inducibility of Dermal Follicle Cells on Silk Fibroin/Sodium Alginate Scaffold for Enhanced Hair Follicle Regeneration

Abstract: The extracellular matrix (ECM) is important for maintaining cell phenotype and promoting cell proliferation and differentiation. In order to better solve the problem of skin appendage regeneration, a combination of mechanical/enzymatic digestion methods was used to self-extract dermal papilla cells (DPCs), which were seeded on silk fibroin/sodium alginate scaffolds as seed cells to evaluate the possibility of skin regeneration/regeneration of accessory organs. Scanning electron microscopy (SEM) graphs showed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 53 publications
0
9
0
Order By: Relevance
“…Therefore, SA is widely concerned in the research of drug carriers and wound repair dressings 18–21 . Our previous studies have shown that SA/SF composite scaffolds have good cell compatibility, can significantly enhance cell adhesion and proliferation, and is an ideal material for repairing soft tissue engineering applications 22–24 . However, the high molecular weight of SA makes it difficult to be degraded into small molecules that can be filtered out by the kidney, which greatly limits its application in the field of tissue engineering 25–28 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, SA is widely concerned in the research of drug carriers and wound repair dressings 18–21 . Our previous studies have shown that SA/SF composite scaffolds have good cell compatibility, can significantly enhance cell adhesion and proliferation, and is an ideal material for repairing soft tissue engineering applications 22–24 . However, the high molecular weight of SA makes it difficult to be degraded into small molecules that can be filtered out by the kidney, which greatly limits its application in the field of tissue engineering 25–28 .…”
Section: Introductionmentioning
confidence: 99%
“…[18][19][20][21] Our previous studies have shown that SA/SF composite scaffolds have good cell compatibility, can significantly enhance cell adhesion and proliferation, and is an ideal material for repairing soft tissue engineering applications. [22][23][24] However, the high molecular weight of SA makes it difficult to be degraded into small molecules that can be filtered out by the kidney, which greatly limits its application in the field of tissue engineering. [25][26][27][28] Studies have shown that the average relative molecular weight of sodium alginate is 507 kDa.…”
Section: Introductionmentioning
confidence: 99%
“…It has good biocompatibility and degradability while showing poor stability in solution. Dong et al applied silk fibroin to make loose and porous scaffolds by adding bioinert sodium alginate to help DPCs complete growth and nutrient exchange and prevent the formation of necrotic cell centers inside the material . Silk fibroin protein can also form regular and uniform pore morphology with sodium alginate through a simple freeze-drying method, and cross-linking reaction can maintain the integrity of scaffolds under a physiological environment, simulating ECM property .…”
Section: Homeostatic Construction Of Hf Organoids Via a Biomaterials ...mentioning
confidence: 99%
“…Alternatively, even a simple method like freeze-drying can cross-link sodium alginate and silk proteins to form a bionic scaffold with a regular uniform pore pattern. 153 This gel material acts as a good mimic of the ECM and promotes the adhesion of DPCs, allowing them to maintain their normal morphology and aggregate growth characteristics. Because of its ability to regulate cell polarization, the functional HF cultured in sodium alginate hydrogel scaffolds are of great significance for the regulation of macrophages to counteract inflammation and ensure cell proliferation after transplantation into the recipient.…”
Section: Homeostatic Construction Of Hf Organoids Via a Biomaterials ...mentioning
confidence: 99%
“…Additionally, dead and live cells were stained using a live-dead cell staining kit (KeyGEN BioTECH, China) and observed using a fluorescence inverted microscope (NIKON, Eclipse TI-U, Japan) on day 7. [55,61] The cells seeded for dead and live staining was at a density of 1 Â 10 3 cells/well.…”
Section: Weight Loss Rate ð%þ ¼ ðWmentioning
confidence: 99%